Dehydroxylation of alcohols for nucleophilic substitution. Issue 51 (6th June 2018) - Chen, Jia; Lin, Jin-Hong; Xiao, Ji-Chang
Abstract : The convenient dehydroxylative substitution of alcohols with various nucleophiles promoted by the Ph3 P/ICH2 CH2 I system under mild conditions is described. Abstract : The Ph3 P/ICH2 CH2 I system-promoted dehydroxylative substitution of alcohols was achieved to construct C–O, C–N, C–S and C–X (X = Cl, Br, and I) bonds. Compared with the previous approaches such as the Appel reaction and Mitsunobu reaction, this protocol offers some practical advantages such as safe operation and a convenient amination process.